Aid Eff ectiveness: New Instrument, New Results? - Emmanuel Frot; Maria Perrotta Berlin (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2009)
Despite a voluminous literature on the topic, the question of whether foreign aid leads to growth is still controversial. To observe the pure effect of aid, researchers used instruments that must be exogenous to growth and explain well aid flows. This paper argues that instruments used in the past do not satisfy these conditions. We propose a new instrument based on predicted aid quantity and argue that it is a significant improvement relative to past approaches. We find a significant and relatively big effect of aid: a one standard deviation increase in received aid is associated with a 1.6 percentage points higher growth rate.
Keywords: F35; O11; 330; Foreign aid; growth; instrumental variables; GMM